2018 14th International Wireless Communications &Amp; Mobile Computing Conference (IWCMC) 2018
DOI: 10.1109/iwcmc.2018.8450524
|View full text |Cite
|
Sign up to set email alerts
|

A MPTCP-based RTT-aware Packet Delivery Prioritisation Algorithm in AR/VR Scenarios

Abstract: This work proposes, describes and performs performance analysis of a Round-Trip Time (RTT)-aware packet delivery prioritisation algorithm (RDPA) for networked Augmented Reality/Virtual Reality (AR/VR) content distribution. In this approach, the proposed algorithm uses the built-in multipath delivery feature of MPTCP. RDPA tracks, identifies and redirects the priority packets through the subflow that presents best opportunities to deliver the content with the lowest latency in the next transmission interval. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…1) Linear regression: For the sake of a light-weight algorithm, this work extends a previous research [22], [27] and simplifies the linear regression applied to PHB report to extract only the slope of the linear regression for any given subflow feature performance (delay, throughout, etc.). Equation 1 describes how the slope is obtained (i.e., in this case, it is the covariance of x and y divided by the sum of squares (variance) of x).…”
Section: B Machine Learning Approachmentioning
confidence: 96%
See 2 more Smart Citations
“…1) Linear regression: For the sake of a light-weight algorithm, this work extends a previous research [22], [27] and simplifies the linear regression applied to PHB report to extract only the slope of the linear regression for any given subflow feature performance (delay, throughout, etc.). Equation 1 describes how the slope is obtained (i.e., in this case, it is the covariance of x and y divided by the sum of squares (variance) of x).…”
Section: B Machine Learning Approachmentioning
confidence: 96%
“…In [21], a network performance enhancement using a Redundant MPTCP (RMPTCP) packet scheduler targeting optimal failover time and smoother latency variations was developed. The authors in [22] demonstrated the benefits achieved by improving the management of the subflow communication while. the work in [23] demonstrates the benefits of an improved MPTCP congestion control.…”
Section: B Mptcpmentioning
confidence: 99%
See 1 more Smart Citation